Website Development as an Information and Material-Sharing Platform for Fiqh of Worship - Dani Pradana Kartaputra; Muhmmad Ramdani Nugraha; Ahmad Lukman Nugraha (Jurnal Bangkit Indonesia, 2025)
Majlis Ta'lim Petuah Bandung, established in 2021, faces challenges in expanding its da'wah reach and improving the efficiency of information management. Currently, they rely on conventional methods such as face-to-face lectures and printed materials, which are limited in reach and accessibility. In the contemporary era of globalization, digitalization plays a pivotal role in the distribution and accessibility of information. Study conducted by other researchers shows that digital platforms have positive results in the propagation of religious education. By leveraging a website as a dedicated da’wah platform, Islamic teachings can be systematically organized, efficiently disseminated, and easily retrieved, overcoming the limitations associated with traditional da’wah methods. In this study, we propose to developing a website as an information platform and a medium for sharing Islamic study materials. This website allows access to study materials anytime and provides discussion features to enhance interaction. Utilizing the Rapid Application Development (RAD) method and technologies such as HTML, CSS, JavaScript, PHP, and MySQL, the website is designed to be user-friendly and tailored to the needs of the community. The results of our study indicate that the website we developed has successfully addressed the challenges of da'wah in the era of globalization by utilizing a website as a da'wah platform.